2013
DOI: 10.1073/pnas.1308215110
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence for the thermophilicity of ancestral life

Abstract: Theoretical studies have focused on the environmental temperature of the universal common ancestor of life with conflicting conclusions. Here we provide experimental support for the existence of a thermophilic universal common ancestor. We present the thermal stabilities and catalytic efficiencies of nucleoside diphosphate kinases (NDK), designed using the information contained in predictive phylogenetic trees, that seem to represent the last common ancestors of Archaea and of Bacteria. These enzymes display e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
197
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(208 citation statements)
references
References 44 publications
8
197
2
1
Order By: Relevance
“…Thus, Ignisphera aggregans (12) and Pyrococcus horikoshii (13) exhibit optimal growth temperature of 92°and 98°C, respectively, whereas another organism isolated from a hydrothermal vent has been reported to grow at 121°C (14). Moreover, reconstructions of ancestral proteins, with amino acid sequences inferred from the sequences of their modern descendants, have been shown to be remarkably thermostable, with melting temperatures ∼30°C higher than those of proteins from their modern descendants (15,16).…”
Section: Hiv-1 Proteasementioning
confidence: 99%
“…Thus, Ignisphera aggregans (12) and Pyrococcus horikoshii (13) exhibit optimal growth temperature of 92°and 98°C, respectively, whereas another organism isolated from a hydrothermal vent has been reported to grow at 121°C (14). Moreover, reconstructions of ancestral proteins, with amino acid sequences inferred from the sequences of their modern descendants, have been shown to be remarkably thermostable, with melting temperatures ∼30°C higher than those of proteins from their modern descendants (15,16).…”
Section: Hiv-1 Proteasementioning
confidence: 99%
“…Since the first ancestral reconstructions by Malcolm et al (1990) and Stackhouse et al (1990), there have now been more than 40 published ASR studies and two common properties exhibited by inferred ancestral proteins/enzymes have emerged: (i) high stability-both thermostability (usually measured as the temperature midpoint of thermal denaturation, T m , or optimum temperature for activity, T opt ) and kinetic stability (measured as the free energy for unfolding, DG z NÀU )- (Akanuma et al 2013;Butzin et al 2013;Gaucher et al 2003Gaucher et al , 2008Groussin et al 2015;Hobbs et al 2012;Miyazaki et al 2001;Perez-Jimenez et al 2011;Risso et al 2013;Watanabe et al 2006a;Watanabe and Yamagishi 2006b) k cat and (ii) high catalytic activity and/or catalytic efficiency (usually expressed as k cat and k cat / K M , respectively) (Stackhouse et al 1990;Akanuma et al 2013;Butzin et al 2013;Groussin et al 2015;Hobbs et al 2012;Perez-Jimenez et al 2011;Risso et al 2013;Watanabe and Yamagishi 2006b;Jermann et al 1995). These increases in stability and catalytic activity compared with contemporary proteins/enzymes can be dramatic, for example Risso et al (2013) reported that their inferred ancestral b-lactamases were more stable than their contemporary descendants by as much as 35°C, and Perez-Jimenez et al (2011) found that their reconstructed ancestral thioredoxins displayed catalytic rate constants up to 30-fold higher than modern thioredoxins at pH 5, as well as being up to 32°C more stable.…”
Section: Introductionmentioning
confidence: 99%
“…This information then can be used to engineer proteins with desired folding properties. ASR has already provided important insights into evolutionary trends in stability, specificity, and other biophysical properties (12)(13)(14)(15)(16)(17)(18)(19)(20).Previously, we used ASR to study the thermostability of the ribonuclease H (RNase H) family and demonstrated divergent trends in thermostability along mesophilic and thermophilic lineages (16). Here we examined the folding mechanism and associated rates of these reconstructed ancestral RNases H. The folding pathway of the two extant homologs, Escherichia coli RNase H (ecRNH) and Thermus thermophilus RNase H Significance Because protein folding is crucial to proper cellular function, there must be evolutionary pressures on how a protein achieves and maintains its folded structure.…”
mentioning
confidence: 99%
“…This information then can be used to engineer proteins with desired folding properties. ASR has already provided important insights into evolutionary trends in stability, specificity, and other biophysical properties (12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%